2016
DOI: 10.2169/internalmedicine.55.6139
|View full text |Cite
|
Sign up to set email alerts
|

Small-cell Lung Cancer in a Young Adult Nonsmoking Patient with Ectopic Adrenocorticotropin (ACTH) Production

Abstract: Cushing's syndrome due to young small-cell lung cancer (SCLC) is recognized as being extremely rare. We herein present the case of a 35-year-old nonsmoking man who presented with thirst and polyuria. Laboratory examinations showed hyperglycemia, hypokalemia and liver enzyme elevation. Imaging examinations revealed the presence of multiple liver tumors and lymph node swelling. The levels of serum neuroendocrine tumor markers were elevated. The patient was diagnosed with SCLC based on the pathological examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In the Cancer and Leukemia Group B (CALGB) database, less than 40% of all patients with extensive stage SCLC were less than 60 years of age [5]. Nevertheless, there are anecdotal reports of young patients with SCLC -some of whom are never smokers -that have arisen in recent years [6][7][8]. In addition, a recent retrospective analysis of Turkish patients, the risk of developing SCLC was reported to be 1.6 times higher among men younger than 45 years of age compared to older men, with an odds ratio of 1.6 [9].…”
Section: Discussionmentioning
confidence: 99%
“…In the Cancer and Leukemia Group B (CALGB) database, less than 40% of all patients with extensive stage SCLC were less than 60 years of age [5]. Nevertheless, there are anecdotal reports of young patients with SCLC -some of whom are never smokers -that have arisen in recent years [6][7][8]. In addition, a recent retrospective analysis of Turkish patients, the risk of developing SCLC was reported to be 1.6 times higher among men younger than 45 years of age compared to older men, with an odds ratio of 1.6 [9].…”
Section: Discussionmentioning
confidence: 99%
“… 2 - 4 The proportion of lung cancer patients aged 50 or younger is estimated to be at most 12%. 5 - 9 In addition, lung cancer has ceased to be an almost exclusively male disease and has become increasingly common among women. Furthermore, this neoplasm occurs more frequently in patients with a history of smoking, and the closing gap in smoking rates between men and women is one of the contributing factors to the increase in the incidence of lung cancer in women.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that among seven patients, conventional chemotherapy did not reduce plasma ACTH levels in two patients. Although five patients showed a transient reduction of ACTH levels reduced concomitantly with decreased tumour size and a duration of 1.5–3 months to reach normal ACTH levels, there have been no reports regarding adrenal insufficiency during chemotherapy to the best of our knowledge ( 1 , 4 , 5 , 6 , 7 , 8 ).…”
Section: Discussionmentioning
confidence: 90%